Perbedaan Pengaruh Metode Bantuan Alat dan Metode Progresif Terhadap Hasil Belajar Gerakan Senam Guling Depan - Daharis, Daharis; Rahmadani, Ahmad (Journal Sport Area, 2018)
This researchaimed to know the difference effect of using media and progressive method. This research took two classes as samples which were 1A and 1B of Health, Physical Education and Recreation Department of Teacher Training and Education Faculty of Universitas Islam Riau. This research design was quasi-experiment. The sample of this research consisted of 2 classes of first semester student which total number of 41 students. The first group was given treatment by using media and another group was given treatment by using progressive method. The research instrument was forward roll test which consisted of three phases such as beginning phase, main phase and closing phase. Data analysis technique was gathered by t-test for two different groups. The result indicated that there were differences of mean score both of those classes. For the sample that was treated by media, the mean score was 8.4 which was higher than the sample that was treated by progressive method with mean score amount 6.4. It means that, the research result shown that the applying media is more effective than progressive method in order to increase students’ forward roll performance of Health, Physical Education and Recreation Department of Teacher Training and Education Faculty of Universitas Islam Riau.